2022
DOI: 10.2106/jbjs.21.00833
|View full text |Cite
|
Sign up to set email alerts
|

Elective Inpatient Total Joint Arthroplasty Case Volume in the United States in 2020

Abstract: Background: Despite known surgical volume reductions in 2020 during the height of the COVID-19 pandemic, no study has fully quantified the impact of the pandemic on the number of elective inpatient total hip (THA) and total knee arthroplasty (TKA) cases. The purpose of the present study was to analyze THA and TKA case volumes in the United States during the COVID-19 pandemic. Methods: The Premier Healthcare Database was utilized to identify adults undergoing primary elective THA or TKA from January 2017 to Dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 13 publications
6
24
0
Order By: Relevance
“…In this study, 82% of AAHKS members reported a dramatic reduction in performing inpatient arthroplasty in late March 2020; this rate peaked in early April at 92%, but dropped to a 23% by mid-June 2020 [ 11 ]. It is not surprising that our findings in UKA mirrored that of other arthroplasty procedures [ 19 ].…”
Section: Discussionsupporting
confidence: 76%
“…In this study, 82% of AAHKS members reported a dramatic reduction in performing inpatient arthroplasty in late March 2020; this rate peaked in early April at 92%, but dropped to a 23% by mid-June 2020 [ 11 ]. It is not surprising that our findings in UKA mirrored that of other arthroplasty procedures [ 19 ].…”
Section: Discussionsupporting
confidence: 76%
“… 15 Heckmann et al used a national inpatient database to assess trends in total hip and knee arthroplasty and found that volume decreased in March and April of 2020 and never increased to pre-pandemic levels throughout the entirety of 2020. 16 …”
Section: Discussionmentioning
confidence: 99%
“…Bedard et al estimated that approximately 30,000 primary and 3,000 revision hip and knee procedures would be cancelled each while restrictions were in place 7 . These cancellations resulted in the overall TJA annual case volume being reduced by nearly 50% in 2020 4 . As a result of elective surgery cancellations, surgeon and hospital revenue for arthroplasty declined by 85% to 90% 6 .…”
Section: Tja Utilization and Financial Lossesmentioning
confidence: 99%